To determine the Influence of Selected School Based Factors on Girls’ Participation Rate in Public Day Secondary Schools in Naivasha Sub-County, Kenya - Waithira Gatere, Janet; Kiumi, Prof. J. Kanjogu; Ngugi, Dr. Margaret (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the influence of selected school based factors on girls’ participation rate in public day secondary schools in Naivasha Sub-County, Kenya. Ex-post facto research design was used in the study. A total of 130 respondents (constituting 26 principals and 104 teachers) from 26 schools were randomly sampled for the study. All the targeted respondents participated in the study giving a response rate of 100%. Simple random sampling technique was used to sample the respondents for the study. Data was collected through a self-administered questionnaire where two sets of questionnaires were developed for data collection; one for principals and the other for class teachers. Descriptive statistics such as means, percentages and frequencies were used to analyze the data while inferential statistics such as simple regression analysis was used to determine the predictive power of school based factors on girls’ participation in school. The study found that three school-level risk factors that had the most negative impact on girls rate of participation in public day secondary schools in the sub-county were: low sense of belonging among girls to their schools, inadequate counseling of girls in schools and low academic performance. Drawing from the computed R2 value (R2 = .426), the study revealed that the selected school level factors were lowering the rate of girls participation in public day secondary schools by almost 43%. The study concluded that that school level factors such as: low sense of belonging among girls to their schools, inadequate counseling of girls in schools and low academic performance had a negative influence on girls’ rate of participation in public day secondary schools in Naivasha Sub-county. It was recommended that public day secondary school educators, specifically principals, counselors and teachers should focus their attention enhancing girls’ participation rate in their schools.